Novel loop-like aromatic compounds: a further step on the road to nanobelts and nanotubes - Rajuri, Venkataramana; Ajami, Dariush; Schaller, Gaston R.; Näther, Christian; Herges, Rainer (Beilstein Journal of Organic Chemistry, 2010)
The synthesis and crystal structural characterization of new compounds 2–6 were accomplished. As a common synthetic methodology, the Diels–Alder reaction was applied to 9,9′,10,10′-tetradehydrodianthracene (TDDA) (7) to furnish the [12]annulenes 2 and 3 [16]annulene 6 and adduct 5.
Keywords: [n]annulenes; Diels–Alder reaction; nanobelts; tetradehydrodianthracene